Tellurium-containing Thiol-peroxidase-like Antioxidants and their Catalytic Mechanism - Capperucci, Antonella; Tanini, Damiano (Current Chemical Biology, 2023)
The development of novel small molecules with effective catalytic antioxidant properties is highly sought after. A wide array of structurally diverse selenium- and tellurium-containing glutathione peroxidase mimics have been studied over the past two decades. Within this arena, organotellurium compounds generally exhibit higher catalytic properties with respect to selenium-containing analogues. Different mechanisms accounting for the thiol-peroxidase-like activity of various classes of organotellurium derivatives have been proposed. This review documents developments in this area and provides an overview of the catalytic mechanisms proposed for the various classes of telluriumcontaining thiol-peroxidase-like-catalysts.
Keywords: GPx-mimics